Good Corporate Governance, Motivasi, Gaya Kepemimpinan dan Kinerja Karyawan - Yanthi, Ni Kadek Ari Kusna; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 31 No 4 (2021)DO - 10.24843/EJA.2021.v31.i04.p09, 2021)
BPD Bali’s bank is a commercial bank engaged in the banking sector. The achievement of Bank BPD Bali's credit targets cannot be separated from employee performance, because with the maximum performance of employees the target set will be achieved. This study aims to determine the effect of GCG, motivation, and leadership style on the performance of employees of Bank BPD Bali’s in Badung Regency. The populations used in this study were 2 branch offices and 7 sub-branch offices in Badung Regency with the determination of the sample using purposive sampling method, the total sampels was 57 respondents. The data analysis technique is multiple linear analysis. The results of the study showed that GCG, motivation, and leadership style had a positive effect on the performance of the employees of Bank BPD Bali’s in Badung Regency, by implementing Good Corporate Governance, motivation and leadership style will improve employee performance. Keywords: Good Corporate Governance; Motivation; Leadership Style; Employee Performance.